Urgent carotid endarterectomy in patients with acute neurological ischemic events within six hours after symptoms onset. (June 2014) - Gajin, P; Radak, Dj; Tanaskovic, S; Babic, S; Nenezic, D
To analyze the outcome of urgent carotid endarterectomy (CEA) performed within less than six hours in patients with crescendo transient ischemic attack (TIA) and stroke in progression. From January 1998 to December 2008, 58 urgent CEAs were done for acute neurological ischemic events – 46 patients with crescendo TIA and 12 patients with stroke in progression. Brain computed tomography (CT) was done prior and after the surgery. Disability level was assessed prior to and after urgent CEA using modified Rankin scale. Median follow-up was 42.1 ± 16.6 months. In the early postoperative period stroke rate was 0% for the patients in crescendo TIA group while in patients with stroke in progression group 3 patients (25%) had positive postoperative brain CT, yet neurological status significantly improved. Mid-term stroke rate was 2.2% in crescendo TIA group and 8.3% in stroke in progression group. In the early postoperative period there were no lethal outcomes, mid-term mortality was 8.3% in stroke in progression while in crescendo TIA group lethal outcomes were not observed. In conclusion, based on our results urgent CEA is a safe and effective treatment option for patients with crescendo TIA and stroke in progression with acceptable rate of postoperative complications.